Prehistoric Myths in Modern Political Philosophy - Widerquist, Karl (Edinburgh University Press, 2017)
This book looks at how modern philosophers pass on myths about prehistory.Why do political philosophers talk so much about the Stone Age? The state of nature, the origin of property, the origin of government, and the primordial nature of inequality and war are popular topics in political philosophy, but are they being used as more than just illustrative examples? Does the best available evidence from archaeology and anthropology support or conflict with the stories being passed on by political philosophers?This book presents a philosophical look at the origin of civilization, examining political theories to show how claims about prehistory are used and presents evidence that much of what we think we know about human origins comes not from scientific investigation but from the imagination of philosophers.